Podwall toughness has no effect on cowpea resistance to the legume pod borer - Oghiakhe, S.; Jackai, L.E.N.; Makanjuola, W.A. (Springer, 1992)
The possibility of the involvement of pod wall toughness in the resistance of cowpea, Vigna unguiculata (L.) Walp., to the legume pod borer, Maruca testulalis was studied. The toughness of non-intact and intact pod wall increased with age, but the rate varied at different growth stages of the pod as well as between cultivars. There was a positive and significant correlation (r = 0.82**) between pod age and pressure required to penetrate pod wall. No significant differences (P > 0.05) were observed in non-intact pod wall toughness between TVu 946 (resistant) and IT82D-716 (susceptible) at all the growth stages tested. However, significant differences (P < 0.05) were observed between these two cultivars for only 6-day-old intact pods where IT82D-716 recorded a higher value than TVu 946. Correlation between pod damage severity by M. testulalis and toughness of non-intact and intact pod wall of these cultivars at different growth stages were not significant. While pod wall toughness would be a desirable trait, it is concluded from this study that pod walls of the cultivars studied did not play any appreciable role on cowpea resistance to the larvae of M. testulalis.